Pengaruh CAR, NPL, ROA, LDR, dan Ukuran Perusahaan terhadap Harga Saham pada Perbankan Konvensional di BEI (2020–2021) - Rohma Septiawati, Rohma Septiawati; Yanti, Yanti; Asih, Asih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The assessment of a company's performance can be reflected in its stock value. In early 2020, particularly on March 2, the impact of the COVID-19 pandemic was felt in Indonesia, leading to a decline in stock prices on the Indonesia Stock Exchange (IDX). This research aims to examine the simultaneous and partial effects of Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), Return On Asset (ROA), Loan to Deposit Ratio (LDR), and Company Size on stock prices in conventional banking companies listed on the IDX during the period of 2020–2021. The research method employed is quantitative, utilizing secondary data from 40 banking companies that meet the criteria out of a total of 45 listed on the IDX. The results of the study indicate that partially, CAR has a positive effect on stock prices, while NPL, ROA, LDR, and Company Size have a negative impact. Simultaneously, CAR, NPL, ROA, LDR, and Company Size collectively have a positive influence on stock prices.